Perspektif Hukum Terhadap Kasus Hak Kekayaan Intelektual dalam Bisnis Teknologi Ditinjau Menurut UU Nomor 16 Tahun 2016 tentang Informasi dan Transaksi Elektronik - Eka Sari, Nandita Cahya; Alamanda, Asri Elies (Fakultas Syariah INSURI Ponorogo, 2023)
This research explores the legal perspective on intellectual property rights (IPR) cases in technology businesses with a focus on the provisions of Article 25 of the Information and Electronic Transactions Law (UU ITE). Article 25 of the ITE Law is the central point in regulating IPR protection in the digital business world in Indonesia. In this context, this research investigates the implementation and impact of Article 25 of the ITE Law on cases of intellectual property rights violations in the era of digital technology. This research uses qualitative descriptive research. This research methodology involves legislative analysis and case studies to identify challenges and opportunities faced by intellectual property rights holders and technology business actors. Using a normative and descriptive legal approach, this research analyzes whether Article 25 of the ITE Law provides adequate protection for intellectual property rights and the extent to which its implementation provides legal certainty for business actors. The research results show that Article 25 of the ITE Law provides a sufficient legal basis for protecting intellectual property rights in technology businesses. However, challenges related to the interpretation and enforcement of Article 25, especially in cases of IPR violations, remain an issue that requires serious attention from policy makers and legal practitioners. This research provides recommendations for improvements and clarifications in the implementation of Article 25 of the ITE Law, as well as the need to increase legal awareness among technology business players to ensure optimal protection of intellectual property rights in this digital era